Epidermal Growth Factor Receptor Mutation In Patients With Non-Small Cell Lung Carcinoma In Fundacion Valle Del Lili, A University Hospital Of Reference In Latin America (2016)
Epidermal Growth Factor Receptor (EGFR) exon 19-deletion and exon 21 L858R mutation is found in 10% of Non-Small Cell Lung Carcinoma (NSCLC) in Caucasians and in 20 to 40% in Asians. The use of Tyrosine Kinase Inhibitors (TKI) in these genetic alterations has demonstrated a greater response and progression free survival in 9-15 months. Objective: To describe the experience in EGFR identification in Fundación Valle del Lili (FVL). Materials and Methods Between June/2013 and Sep/2015, 95 samples were analyzed. A microdissection of tumor areas was performed as well as DNA extraction with QIAamp FFPE Kit(Qiagen®) and amplification of exons 18, 19, 20 and 21 by PCR. It was visualized through microfluidic electrophoresis with Agilent Bioanalyzer® System. Results 98 samples were analyzed. Amplified DNA was obtained in 97% (95) of the cases. The mean age was 65,4±12 years, 63,2% (60) females and 36,8% (35) males. The mutation was observed in 25% (24), exon 19 in 10,5% and exon 21 in 14,7%. 83,1% of the tumors were adenocarcinomas, 70,5% in stage IV and 29% of the cases with a mutation was receiving TKI. Mortality was 14,7% .